2018
DOI: 10.1038/s41419-018-0367-6
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 positively regulates aerobic glycolysis via the EGLN2/HIF-1α axis and indicates prognosis in pancreatic cancer

Abstract: Patients with pancreatic ductal adenocarcinoma have much worse prognoses, and much effort has been directed toward understanding the molecular biological aspects of this disease. Accumulated evidence suggests that constitutive activation of the Wnt/β-catenin signalling contributes to the oncogenesis and progression of pancreatic cancer. Transcription factor 7-like2/transcription factor 4 (TCF7L2/TCF4), a β-catenin transcriptional partner, plays a vital role in the Wnt/β-catenin signalling pathway. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Transcription factor 7-like2/transcription factor 4 (TCF7L2/TCF4) plays a vital role in Wnt/β-catenin signaling pathway. It was identified as a transcriptional factor that was responsible for Egl-9 family hypoxia inducible factor 2 (EGLN2) silencing, which leads to upregulation of HIF-1α and finally affects glycolysis reprogramming [ 43 ]. There is a positive-feedback regulation between HIF-2α and β-catenin that HIF-2α/β-catenin complex could upregulate the activity of β-catenin and stabilize and increase transcriptional activity of HIF-2α.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor 7-like2/transcription factor 4 (TCF7L2/TCF4) plays a vital role in Wnt/β-catenin signaling pathway. It was identified as a transcriptional factor that was responsible for Egl-9 family hypoxia inducible factor 2 (EGLN2) silencing, which leads to upregulation of HIF-1α and finally affects glycolysis reprogramming [ 43 ]. There is a positive-feedback regulation between HIF-2α and β-catenin that HIF-2α/β-catenin complex could upregulate the activity of β-catenin and stabilize and increase transcriptional activity of HIF-2α.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also examined the role of glycolysis in prediction of patient survival. For example, higher TCF7L2 expression predicted worse prognosis in pancreatic cancer ( 19 ). Four glycolysis-related genes (GRGs) (AGRN, AKR1A1, DDIT4, and HMMR) were identified as closely related to the clinical outcome in patients with lung adenocarcinoma ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…During Wnt activation, TCF7L2 was activated by Wnt ligands or certain growth factors (such as insulin and IGF-1), and further participated in many Wnt-related biological processes [6]. Previous study suggested that TCF7L2 may stimulate the proliferation of pancreatic β-cells and facilitate the production of the incretin hormone glucagon-like peptide-1 in intestinal endocrine cells [79], but the molecular mechanisms underlying are far from understood. TCF7L2 also plays an important role in conveying Wnt signaling pathway in regulating gene expression, and a highly significant proportion of genes bound by TCF7L2 are known disease-associated loci [10, 11].…”
Section: Introductionmentioning
confidence: 99%